Des réseaux d’agriculteurs en faveur de l’environnement en France - François Laurent; Rosa Vieira Medeiros (Cybergeo)
French agriculture is subject to criticism because of its impact on natural resources, the changes it brings to the countryside, and the sometimes disputed quality of its productions. Faced with the expectations of society and the pressure of regulations, some farmers have decided to organize themselves in networks to propose alternative systems of production. A true dynamic is at work among these minority farmers who are seeking to disseminate their experiences by creating new bonds within the farming population. All claim a greater sustainability in the modes of production, but the degree of challenge to the conventional systems varies according to their conceptions of their trade and their place in society. In this paper, we analyze four alternative networks by examining the recommendations they put forward, the types of production in question, the territorial base of the networks, and the links they establish with the society around them. The experiences reported by farmers in the west of France will enable us to grasp the extent of their activities and the interest to be found in these practices, but also the difficulties they encounter.